El vencimiento del contrato, de la prórroga o de la renovación, como causal de terminación del contrato de arrendamiento (2004)
This article contains a group of juridical reflections regarding the leasing contract of real estates; throughout the context of the Colombian juridical ordinance. In particular; it approaches the issues concerning the juridical viability that the landlord can unilaterally terminate the leasing contact; when invoking; as a cause; the mere term-expiration initially agreed upon by the parties; or the expiration of the respective extension or its renewal. Parralelly; a study will be made over the viability that the landlord can validly invoke such circumstances as a cause to contract termination.